Role of LncRNA MALAT-1 in hypoxia-induced PC12 cell injury via regulating p38MAPK signaling pathway. (23rd March 2018) - Yang, Lin; Xu, Fei; Zhang, Miao; Shang, Xiao-Ying; Xie, Xin; Fu, Tao; Li, Jian-Ping; Li, Hong-Lin
Highlights: MALAT-1 was up-regulated in hypoxia-induced PC12 cells. MALAT-1 can reduce the survival and increase the apoptosis of PC12 cells. MALAT-1 can activate the p38MAPK pathway to aggravate the injury of hypoxia-induced PC12 cells. MALAT-1 is expected to be a new therapeutic target for hypoxia-induced cell injury. Abstract: Objective: To investigate the role of LncRNA MALAT-1 in hypoxia-induced cell injury. Methods: Pheochromocytoma-12 (PC12) cells were divided into seven groups: Control group, Hypoxia group (Cells treated with CoCl2 ), MALAT-1 group (Hypoxic cells treated with MALAT-1), NC group (Hypoxic cells treated with empty plasmid), MALAT-1 siRNA group (Hypoxic cells treated with siRNA MALAT-1), SB203580 group (Hypoxic cells treated with p38MAPK inhibitor), and MALAT-1 + SB20358 group. The content of reactive oxygen species (ROS), malondialdehyde (MDA), super oxide dismutase (SOD) and lactate dehydrogenase (LDH) was determined. Cell viability was detected by MTT assay. Apoptotic cells were observed by Hoechst 33258 and TUNEL staining assay. Mitochondrial membrane potential (MMP) was measured using JC1 vital dye. Results: The decreased cell viability and increased expressions of MALAT-1 and p-p38 were observed in hypoxic PC12 cells time-dependently ( P <  0.05). Besides, hypoxic PC12 cells had an elevation in p-p38, ROS, MDA and LDH with the increased apoptotic cells, but a reduction in SOD and MMP, and these similar changes were more obvious in those hypoxic cells treated with MALAT-1 when compared with Controls (all P <  0.05). However, the hypoxic PC12 cells treated with SB203580 and MALAT-1 siRNA led to opposite results compared with MALAT-1 group (all P  < 0.05). Importantly, SB203580 could reverse the function of MALAT-1 in aggravating the hypoxia injury of PC12 cells. Conclusion: MALAT-1 can promote the apoptosis and oxidative stress of PC12 cells by activating p38MAPK pathway, thus aggravating the damage of PC12 cells induced by chemical hypoxia.